2018
DOI: 10.1002/tesj.379
|View full text |Cite
|
Sign up to set email alerts
|

ESL teachers' multiple intelligences and teaching strategies: Is there a linkage?

Abstract: The multiple intelligences (MI) theory has been widely applied to literacy education and English as a second language (ESL) teaching in informing curriculum development and instructional strategies. Using the framework that intelligence shapes human behavior, this study examines the correlations between ESL teachers' MI preferences and their use of MI‐framed teaching strategies in the ESL classroom. Data collected from 67 ESL teachers in a midwestern U.S. state by completing the Intelligence Index and the MI‐F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…When testing MI theory to ascertain if it holds validity in assessing instructional strategies aligned to its concept of multiple intelligences, many studies have found no widespread statistical correlation or validity in MI theory’s concepts of multiple intelligences and instructional strategies aligned to those purported intelligences (e.g., Waterhouse, 2006 ; Willingham et al, 2015 ; Luo and Huang, 2019 ). However, some case studies have found statistical significance for some of the MI domains (e.g., Dolati and Tahriri, 2017 ; Yidana et al, 2022 ), or partial significance for one but not the other domains (e.g., Rogowsky et al, 2015 ).…”
Section: Comparative Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…When testing MI theory to ascertain if it holds validity in assessing instructional strategies aligned to its concept of multiple intelligences, many studies have found no widespread statistical correlation or validity in MI theory’s concepts of multiple intelligences and instructional strategies aligned to those purported intelligences (e.g., Waterhouse, 2006 ; Willingham et al, 2015 ; Luo and Huang, 2019 ). However, some case studies have found statistical significance for some of the MI domains (e.g., Dolati and Tahriri, 2017 ; Yidana et al, 2022 ), or partial significance for one but not the other domains (e.g., Rogowsky et al, 2015 ).…”
Section: Comparative Literature Reviewmentioning
confidence: 99%
“…Some studies that emphasized qualitative observation in assessment practices and semantically infer that the use of the word intelligences is practically synonymous with preferences suggest more positive results, though not generalizable (e.g., Mokhtar et al, 2008 ; Baş and Beyhan, 2010 ). However, when testing MI theory’s application in how assessment of student learning is conducted in an MI theory-based curriculum, findings from studies suggest ambiguity or little scientific foundation for MI theory ( Luo and Huang, 2019 ). This, taken together with other studies that raise questions of MI theory’s generalizable significance or lack of correlation between it and assessment strategies based upon it ( Waterhouse, 2006 ; Willingham et al, 2015 ), provide additional support for explicit direct instruction (EDI) in the teaching of English as a second language, as well as in the teaching of several other content areas.…”
Section: Comparative Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…GI theory extends the traditional view of intelligence beyond verbal-linguistic and logical-mathematical abilities. Perhaps it would be more accurate to describe it as an educational philosophy or attitude to changing the way people think about learning (Luo & Huang, 2019).…”
Section: Introductionmentioning
confidence: 99%